The effectiveness of a proposed educational program according to the constructivist social interaction theory in achievement among students of basic education colleges. - Abid Murshid, Saja; Hatif Obaid, Reyadh (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to: Build a proposed educational program according to the constructive, social, and interactive theory of achievement for students of basic education colleges. To achieve the research goal, the two researchers hypothesized the following zero hypothesis: There are no statistically significant differences at the level of significance (05, 0) between the average levels of achievement of experimental group students who study using the proposed educational program prepared according to the interactive social constructive theory, and the average score of the control group students who They study the same subject in (the Normal method) with a post-achievement test, and to achieve this the researchers chose an experimental design with partial control, as was chosen intentionally by the College of Basic Education to conduct the experiment, and the research sample consisted of (60) students with a rate of (30) students A student of the experimental group and (30) male and female students of the control group. The experimental group studied the proposed educational program according to the interactive social constructive theory, and the control group studied in the Normal method, and the researcher verified the characteristics of the psychometric test of the test. The end of the experiment, the researcher applied the post achievement test to the two groups, after that the results were analyzed and showed the superiority of the experimental group who studied according to the educational program over the control group who studied in the usual way.